Influence of Work Discipline and Motivation on Work Performance of Hospital Employees during the Coronavirus Disease 2019 Pandemic - Linda E. Mantiri; Martha M. Kaseke; Jeini E. Nelwan; Oksfriani J. Sumampouw (e-CliniC, 2022)
Abstract: Job performance is a description of the level of achievement of the implementation of a policy in realizing the goals, objectives, mission and vision of the organization. The existence of the corona virus disease 2019 (Covid-19) pandemic demands that the performance of employees must better than before, especially in hospitals. Performance is influenced by various factors including discipline and work motivation. This study aimed to analyze the influence of discipline and work motivation on the employees' performance at RSUD Dr. Sam Ratulangi Tondano. This was a quantitative study with a cross-sectional design. This study was conducted at RSUD Dr. Sam Ratulangi Tondano from March to June 2021 using a questionnaire as instrument. Data were analyzed multivariately. Subjects were 126 employees The results showed that most respondents had good performance (97.6%), good work discipline (94.4%), and good work motivation (77.0%). The multivariate analysis showed that work discipline had a significant effect on employee performance (p=0.000), meanwhile, motivation did not have a significant effect on it (p=0.192). An increase of 1 value of discipline would be associated with an increase of performance by 0.492. In conclusion, discipline is the influencing factor of the performance of employees at RSUD Dr. Sam Ratulangi Tondano during the Covid-19 pandemicKeywords: performance; discipline; motivation; hospital employee; Covid-19Â Abstrak: Kinerja adalah gambaran mengenai tingkat pencapaian pelaksanaan suatu kebijakan dalam mewujudkan sasaran, tujuan, misi dan visi organisasi. Adanya pandemik Corona Virus Disease 2019 (Covid-19) menuntut kinerja pegawai khususnya di rumah sakit semakin baik. Kinerja dipengaruhi oleh berbagai faktor termasuk disiplin dan motivasi kerja. Penelitian ini bertujuan untuk menganalisis pengaruh disiplin dan motivasi kerja terhadap kinerja pegawai Rumah Sakit Umum Daerah Dr. Sam Ratulangi Tondano. Jenis penelitian ialah kuantitatif dengan desain potong lintang. Penelitian ini dilaksanakan di RSUD Dr. Sam Ratulangi Tondano pada Maret-Juni 2021. Sebanyak 126 pegawai menjadi subyek penelitian ini. Instrumen penelitian ini yaitu kuesioner. Data dianalisis secara multivariat. Hasil penelitian menunjukkan bahwa responden paling banyak memiliki kinerja yang baik (97,6%), disiplin kerja yang baik (94,4%), dan motivasi kerja yang baik (77,0%). Hasil analisis multivariat menunjukkan disiplin kerja berpengaruh bermakna terhadap kinerja pegawai (p=0,000) sedangkan pengaruh motivasi kerja tidak bermakna (p=0,192). Setiap kenaikan 1 nilai disiplin akan disertai kenaikan kinerja sebesar 0,492. Simpulan penelitian ini yaitu disiplin merupakan faktor yang berpengaruh terhadap kinerja pegawai di RSUD Dr. Sam Ratulangi Tondano pada masa pandemi Covid-19.Kata kunci: kinerja; disiplin; motivasi; pegawai rumah sakit; Covid-19